2015
DOI: 10.1093/asj/sjv198
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the American Society of Anesthesiologists Physical Status Classification System and Caprini Risk Assessment Model in Predicting Venous Thromboembolic Outcomes in Plastic Surgery Patients

Abstract: 4 Risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
2
29
0
2
Order By: Relevance
“…The multivariate analysis in the present study revealed that knee surgery with TKA or UKA is one of the factors associated with the preoperative DVT. Besides knee surgery, the other factors found to be associated with preoperative DVT in our analysis were advanced age, ASA physical status, and malignancy, which were consistent with the previously reported risk factors of postoperative VTE [ 3 , 20 ]. In patients with knee osteoarthritis, restricted knee flexion and extension due to knee pain or limited joint range of motion may result in DVT prevalence in the veins of the lower extremities.…”
Section: Discussionsupporting
confidence: 91%
“…The multivariate analysis in the present study revealed that knee surgery with TKA or UKA is one of the factors associated with the preoperative DVT. Besides knee surgery, the other factors found to be associated with preoperative DVT in our analysis were advanced age, ASA physical status, and malignancy, which were consistent with the previously reported risk factors of postoperative VTE [ 3 , 20 ]. In patients with knee osteoarthritis, restricted knee flexion and extension due to knee pain or limited joint range of motion may result in DVT prevalence in the veins of the lower extremities.…”
Section: Discussionsupporting
confidence: 91%
“…The multivariate analysis in the present study revealed that knee surgery with TKA or UKA is one of the factors associated with the preoperative DVT. Besides knee surgery, the other factors found to be associated with preoperative DVT in our analysis were advanced age, ASA physical status, and malignancy, which were consistent with the previously reported risk factors of postoperative VTE [3,19]. In patients with knee osteoarthritis, restricted knee exion and extension due to knee pain or limited joint range of motion may result in DVT prevalence in the veins of the lower extremities.…”
Section: Discussionsupporting
confidence: 90%
“…The Caprini score (CS) is widely used to assess for surgical patients (Caprini, 2005). It was validated in for plastic and reconstructive surgery patients in several large cohort studies and demonstrated that higher CS was associated with a higher incidence of VTE (Pannucci et al., 2011; Shaikh et al., 2016; Yago et al., 2019). CS is recommended in American Society of Clinical Oncology (ASCO) Guidelines for patients undergoing breast surgery (Surgeons, 2016).…”
Section: Introductionmentioning
confidence: 99%